Formulation and Evaluation of Sustained Release Tablets Using Prunus armeniaca (L.) and Prunus domestica (L.) Gums: Sastained Release Tablets From Prunus - Mir Azam Khan,; Waqar Ahmad,; Salimullah Khan,; Haroon Rahim,; Roohullah,; Fazli Amin, (Iranian Journal of Pharmaceutical Sciences, 2012)
The plant gums obtained from Prunus armeniaca and Prunus domestica (Familym Rosaceae) were studied for their sustained release potential in comparison with hydroxypropyl methyl cellulose (HPMC), a semi-synthetic matrix polymer, using diclofenac sodium. Matrix tablets of diclofenac sodium were prepared using different ratios of gum alone and in combination (i.e. 1:1) with diclofenac sodium and other excipients. The formulated matrix tablets were evaluated for their thickness, hardness, weight variation, friability, drug content and in vitro release studies. These studies demonstrated that P. armeniaca and P. domestica gums used alone could not control drug release efficiently, however, extended drug release (up to 10 hours) was obtained when both gums were used in combination (1:1). The dissolution data was fitted into zero order, first order, Higuchi and Korsmeyer equation, which dictated that the release mechanism is diffusion as well as erosion controlled-drug release. FTIR studies showed that there was no interaction between drug and plant gums used. Among various formulated batches, F-5 did not significantly differ from F-7 and commercially available formulation (Voltral SR®, Novartis Pharma, Pakistan) with respect to drug release.